PENGARUH EDUKASI MENGGUNAKAN VIDEO TENTANG HIV/AIDS TERHADAP PENGETAHUAN DAN SIKAP REMAJA DI KECAMATAN SANANWETAN - Sabhita, Dewanty; Winarni, Sri; Djuwadi, Ganif (Jurnal Pendidikan Kesehatan (e-Journal), 2022)
Health education about HIV AIDS for adolescents is very important because the incidence of HIV AIDS increases every year. The province of East Java is the province with the second highest number with the number of cases 62,392, which are spread across several cities, one of which is the City of Blitar. In the city of Blitar, there are 49 people with HIV AIDS with a vulnerable age of 21 until 30 years who may have been exposed since adolescence. This research is a quantitative study using a quasi experimental method with a pretest-posttest design on the knowledge and attitudes of adolescents in the Class 1 LPKA Special Guidance Institute with a population of 30 teenagers. And sampling using a total sampling of 30 respondents. The instrument used in data collection was a questionnaire. The study was carried out from 10 to 16 February 2022. The data analysis used was the Wilcoxon Signed Rank analysis with same with 0.05, it was found that before and after being given health education using video, the knowledge of adolescents in the 0Percent good category increased to 66.7Percen, the moderate category 33.3Percen remained, the less category 66.7 decreased to 33.3Percen. And for the attitude of adolescents before and after being given health education, namely the negative category, 86.7Percen decreased to 0Percen, and for the positive category from 13.3Percen increased to 100Percen. This is evidenced by the results of the Wilcoxon test with a value of p same with 0.001More than 0.05. The results showed that the health education method using video had an effect on the knowledge and attitudes of adolescents. Video media in this study can be used as additional media as a source of information to adolescents about HIV AIDS